2020
DOI: 10.1080/15230430.2020.1824558
|View full text |Cite
|
Sign up to set email alerts
|

Warmer temperatures promote shrub radial growth but not cover in the central Canadian Arctic

Abstract: We assessed the response of Salix richardsonii, a deciduous shrub, to climate change by determining the combination of climatic factors that regulated its growth over the past half-century. We tested whether increasing arctic temperatures promote shrub growth and increased cover. We analyzed fifty-four stems (out of seventy sampled) from S. richardsonii shrubs near the Walker Bay research station in Nunavut, Canada (68°21′ N, 108°05′ W) and surveyed shrub cover in 1996 and 2010. We measured annual growth rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…2)-reiterates patterns elsewhere in the High Arctic (Elmendorf, Henry, Hollister, Björk, Boulanger-Lapointe et al 2012;Kapfer & Grytnes 2017;cf. Hill & Henry 2011), as well as at Walker Bay, 140 km to the south-west (Buchkowski et al 2020). Declines in mosses-in my study, manifest in both cover and frequency, albeit marginally significant (Table 1)-is another widespread trend (Elmendorf, Henry, Hollister, Björk, Bjorkman et al 2012;Elmendorf, Henry, Hollister, Björk, Boulanger-Lapointe et al 2012;Bjorkman et al 2020).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…2)-reiterates patterns elsewhere in the High Arctic (Elmendorf, Henry, Hollister, Björk, Boulanger-Lapointe et al 2012;Kapfer & Grytnes 2017;cf. Hill & Henry 2011), as well as at Walker Bay, 140 km to the south-west (Buchkowski et al 2020). Declines in mosses-in my study, manifest in both cover and frequency, albeit marginally significant (Table 1)-is another widespread trend (Elmendorf, Henry, Hollister, Björk, Bjorkman et al 2012;Elmendorf, Henry, Hollister, Björk, Boulanger-Lapointe et al 2012;Bjorkman et al 2020).…”
Section: Discussionsupporting
confidence: 46%
“…On south-eastern Victoria Island, a region undergoing rapid climate change (Panchen 2016;Bush & Lemmen 2019;Buchkowski et al 2020), I discovered pronounced shifts in vegetation after three decades: a marked increase in graminoids, along with substantial declines in Dryas integrifolia, Polygonum viviparum and Saxifraga oppositifolia (Table 1, Figs. 2, 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, based on the results of Baral et al [40], who demonstrated that climate-tree growth relationships were stronger when using BAI rather than standardized RW in short chronologies, we believe that the use of BAI might be of high interest when analyzing shrub species' growth rings. Indeed, even though BAI measurement has been used mainly with trees, it remains only marginally used for shrub species [22,23,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…A secondary objective was to determine if BAI estimations (i.e., calculated from raw ring width measurements) are correlated with the actual measurements of BAI (i.e., measured on scanned cross-sections using image analysis) for B. glandulosa. Indeed, both approaches have been used in previous studies but have never been compared (calculated: [37,40,42]; measured: [22,41]). Calculating BAI from RW measurements is significantly faster, but might generate inaccurate values in the presence of eccentric growth forms or irregular rings [23].…”
Section: Introductionmentioning
confidence: 99%